Portal of Security and Safety Engineering as a Tool to Increase the Sustainable Development of Higher Education in Security in the European Union and Beyond - Tomas Lovecek; Jozef Ristvej; Katarina Kampova; Juraj Vaculík; Roberto Gamboa; Adam Zagorecki (Communications - Scientific letters of the University of Zilina, 2013)
In this article we describe a project “Competency Based e-Portal of Security and Safety Engineering” – eSEC portal approved by The Education, Audio-visual and Culture Executive Agency (EACEA), developed in the period between 10/2009 and 10/2012. The eSEC portal is one of 10 centralised multilateral projects approved in 2009 by EACEA and only one with the University of Zilina as a coordinator, with total budget 356.138 Euros. The EACEA is responsible for the management of certain elements of the EU's programs in the fields of education and culture. The idea for the eSEC project originated from the demand to increase the quality of education in the field of security and safety. One of the key problems of the education is disparity between the knowledge received from educational institutions and the practical requirements. It is necessary to redefine how students are prepared for the challenges of the labour market: identifying competencies that are currently indemand and how it would be possible to link the educational systems of various institutions more efficiently. The aim of the eSEC project was to develop the competencies of students, teachers, researchers and professionals working in the field of security and safety, within the EU and the world. To achieve these objectives, an electronic portal was developed at www.esecportal.eu. The portal was launched in May 2012, hopefully starting the way to become an established and well known Internet portal on the security and safety education.